Improved furfural tolerance in Escherichia coli mediated by heterologous NADH-dependent benzyl alcohol dehydrogenases. Issue 10 (27th May 2022) - Willson, Benjamin James; Herman, Reyme; Langer, Swen; Thomas, Gavin Hugh
Abstract : While lignocellulose is a promising source of renewable sugars for microbial fermentations, the presence of inhibitory compounds in typical lignocellulosic feedstocks, such as furfural, has hindered their utilisation. In Escherichia coli, a major route of furfural toxicity is the depletion of NADPH pools due to its use as a substrate by the YqhD enzyme that reduces furfural to its less toxic alcohol form. Here, we examine the potential of exploiting benzyl alcohol dehydrogenases as an alternative means to provide this same catalytic function but using the more abundant reductant NADH, as a strategy to increase the capacity for furfural removal. We determine the biochemical properties of three of these enzymes, from Pseudomonas putida, Acinetobacter calcoaceticus, and Burkholderia ambifaria, which all demonstrate furfural reductase activity. Furthermore, we show that the P. putida and B. ambifaria enzymes are able to provide substantial increases in furfural tolerance in vivo, by allowing more rapid conversion to furfuryl alcohol and resumption of growth. The study demonstrates that methods to seek alternative cofactor dependent enzymes can improve the intrinsic robustness of microbial chassis to feedstock inhibitors.